Patients' Perception of Bone and Tissue Excision, and the Size and Weight of Prostheses at Total Knee Arthroplasty - Rossi, Benjamin; Jayasekera, Narlaka; Kelly, Fionnuala Anne; Eyres, Keith (The Surgery Journal, 2017)
The aim of this study is to ascertain patients' perception of the amount of bone and tissue excision and size and weight of their implanted prostheses at total knee arthroplasty (TKA). To our knowledge, no prior study in the English orthopaedic literature has analyzed these parameters against patient perception of TKA. In a prospective study of eight consecutive TKA (six primary and two single-stage revision TKA procedures) by a single surgeon, patients estimated the weight of their implanted knee. We assessed actual weights of their implants and bone cement. Patients estimated the size of their prostheses by sketching the tibial and femoral bone cuts upon a printout of an anteroposterior and lateral radiographs of their preoperative knee. We utilized an articulated plastic model knee for patient reference. Our study shows almost half a kilogram of weight is added postoperatively to the surgical site as a result of tissue excision, explanted material, and implanted prosthesis and cement. All patients overestimated the weight of their implanted prostheses and extent of bone excision. Thus, even ‘well-informed’ patients overestimate their bone resection and weight of implanted prosthesis at TKA. We postulate such misconceptions among TKA patients are common, and may impact negatively upon patient perception of TKA, their postoperative recovery and outcome.
Keywords: knee arthroplasty; prostheses; bone excision; patients' perception